Leaf gas exchange and chlorophyll index in guava fertirrigated with bovine biofertilizer and nitrogen (Research, Society and Development, 2020)
The objective of this work was to evaluate the influence of fertirrigation with nitrogen and liquid bovine biofertilizer on gas exchange and leaf chlorophyll index of 'paluma' guava (Psidium guajava L.). The experimental design was randomized blocks with treatments distributed in a factorial arrangement (2 × 4) referring to mineral fertilizing with N (50% and 100% of N recommended) and biofertilizer concentrations (0, 2.5, 5.0 and 7.5% of the fertirrigated volume). Variables evaluated were chlorophyll a (Chl a), chlorophyll b (Chl b), total chlorophyll indexes (Chltotal), internal CO2 concentration (Ci), stomatal conductance (gs), transpiration (E), net photosynthesis (A), instant carboxylation efficiency (iCE) and water use efficiency (WUE). The biofertilizer significantly affected Chl a, Chl b, Chltotal, A, gs and E, with quadratic polynomial adjustment of the results. However, there was no effect of N fertilization and interaction between the factors. Maximum index of Chltotal was 32.31 obtained with the estimated dose of 3.8% of the biofertilizer; while A, gs and E presented maximum responses of 19.09 µmol of CO2 m-2 s-1, 0.28 mol of H2O m-2 s-1 and 4.93 mmol of H2O m-2 s-1, with estimated doses of 3.6%, 3.6%, and 3.7%, respectively. Generally, liquid bovine biofertilizer applied via fertirrigation affects positively the photosynthetic responses in 'paluma' guava, however, with decreasing effects for doses above 3.8%.